2017
DOI: 10.1186/s12891-017-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyaluronic acid combined with anti-inflammatory drugs compared with hyaluronic acid alone, in clinical trials and experiments in osteoarthritis: a systematic review and meta-analysis

Abstract: BackgroundThe objectives are to compare the efficacy of intra-articular hyaluronic acid (IA-HA) alone and in combination with anti-inflammatory drugs (IA-HA + AI), corticosteroids (CS) or non-steroidal anti-inflammatory drugs (NSAIDs) in clinical trials and in vivo and in vitro studies of osteoarthritis (OA).MethodsData in the BIOSIS, CINAHL, Cochrane Library, EMBASE and Medline databases were collected and analyzed. Random effects models were used to compute the effect size (ES) of the mean difference in pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
1
24
0
3
Order By: Relevance
“…They found that, Intra-articular Hyaluronic acid and anti-inflammatory drugs had greater efficacy for pain relief than Intra-articular Hyaluronic acid alone. 10 In our study, we used Methyl prednisolone with Hyaluronic acid and also found better efficacy of combination therapy in terms of pain relief and function improvement.…”
Section: Discussionmentioning
confidence: 65%
“…They found that, Intra-articular Hyaluronic acid and anti-inflammatory drugs had greater efficacy for pain relief than Intra-articular Hyaluronic acid alone. 10 In our study, we used Methyl prednisolone with Hyaluronic acid and also found better efficacy of combination therapy in terms of pain relief and function improvement.…”
Section: Discussionmentioning
confidence: 65%
“…Thus, not only pain relief and suppression of inflammation should be addressed, but also cartilage repair. Recent reports have investigated the combined effects of HA and anti-inflammatory drugs (CSs or NSAIDs) [66,67] in order to develop more effective OA treatments. We evaluated the combined effects of HA with low concentrations of Dex and therapeutic concentrations of Dic or Ace on CSE-impaired chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the protective potential of oral SNO supplementation differs from that of IAHA in many aspects (route, dose frequency, and mechanism of action). But the combination of both therapeutic models, like IA corticosteroid/anti-inflammatory drugs combined with IAHA, can lead to significant improvement of the clinical outcome of either agent alone [30]; this however only provides short duration, and is not feasible for persisting injection. Therefore, we sought to determine the role of oral SNO as an adjuvant in combination with IAHA injections and compare the effectiveness in the OA rat model.…”
Section: Introductionmentioning
confidence: 99%